EXPERIMENTAL ANALYSIS OF THE INFLUENCE OF HEAT SINK GEOMETRIC PARAMETERS ON NATURAL CONVECTION - Silva, V. A.; Anselmo, B. C. S.; Silva, A. L. F. L.; Silva, S. M. M. L. (Revista de Engenharia Térmica, 2016)
In this work, the steady state heat transfer by natural convection in heat sinks with rectangular fins positioned vertically and horizontally was studied. The heat transfer by radiation was also considered. Several analyses were performed to determine the optimal number and position of the sensors used to measure the temperature on the heat sinks horizontally and vertically positioned. These analyses confirmed an almost uniform temperature distribution in the heat sink. This uniformity allowed the use of thermocouples only in the center of the heat sink. Twelve heat sinks were designed to study how their geometric parameters such as height, spacing and thickness of the fins, influence the heat transfer by free convection. In addition, in this work, two correlations using the dimensionless parameters Nusselt and Rayleigh are proposed. These correlations were obtained by using the results from the 12 heat sinks vertically and horizontally positioned considering a temperature range between 20 °C and 100 °C. Furthermore, studies were done to identify which of the 12 analyzed heat sinks managed to remove the greatest amount of heat in a given temperature range. The results were compared with those obtained from empirical correlations found in literature.